Dîvânu’t-tel’aferî - 880-01 Muhammed b. Yusuf b. Mesud b. Bereke Şihabüddin eş-Şeybânî et-Tel’aferî, 1197-1276. (Beyrut Beyrut)
3 kitap 1 ciltte (1. kitap 24 sayfa, 2. kitap 62 sayfa, 3. kitap 88 sayfa)